Effects of Digitalization on Energy Efficiency: Evidence From Zhejiang Province in China - Niu, Yi; Lin, Xiangyi; Luo, Hongyun; Zhang, Jianhua; Lian, Yinghuan (Frontiers in Energy Research, 2022)
The rapid development of digitalization has brought disruptive changes to the economy and life. The effect of digitalization on energy efficiency is explored using a time series dataset from 2003–2019 in Zhejiang Province and is discussed in four aspects: physical foundation, participant, medium, and pathway. The ridge regression estimation results show that digitalization has a positive effect on energy efficiency. Network infrastructure, communication service development, information technology industry development, and digital technology innovation have various degrees of positive contribution to energy efficiency. This study provides valuable insights for improving energy efficiency. Enhancing the physical foundation, participant, medium, and pathway of digitalization are confirmed as ways to improve energy efficiency. This study enriches the theory of energy efficiency in the context of digitalization and has practical implications for improving regional energy efficiency in the digital era.